ANALISIS IMPLEMENTASI GOOD CORPORATE GOVERNANCE TERHADAP KINERJA SDM MELALUI ORGANIZATIONAL COMMITMENT - Mutamimah .; Phradiansah . (Jurnal Ekonomi dan Bisnis, 2014)
Good corporate governance is one of concepts which becomes solution for the deterioration of employee performance in Indonesia. The contributions such as participation, transparency, responsbility, and fairness are essential factors which affect employee performance. The good organizational commitment could be used as the measurement for the implementation of proper good corporate governance. The objective of this study is to know the impact of good coporate governance and employee performance which is moderated by organizational commitment in State Hospital of Konawe Regency. The population was 214 civil servants who work inState Hospital of Konawe Regency. The sample was 68 respondents which used Proporsioal Sampling technique. The analysis used structural equation modeling with Partial Least Square (PLS) alternative method. The result shows that: (1) Participation gives positive and significant impact on improving employee performance. It means that if participation improves so that employee performance also improves. (2) Transparency gives positive and unsignificant impact on employee performance. It means that it has correlation, but low transparency doesn’t improve employee performance. (3) Accountability gives positive and unsignificant impact onemployee performance. It means that it has correlation but low accountability doesn’t improve employee performance. (4) Fairness gives postive impact in improving employee performance. (5) Organizational commitment gives positive result, but it doesn’t give impact on moderating the participation influence toward employee performance in improving employee performance. It means that the correlation of organizational commitment moderation doesn’t strengthen the correlation of participation toward employee performance. (6) Transparency gives negative andsignificant impact in improving employee performance which is moderated by organaizational commitment. It means that the decreasing of transparency affects the improvement of employee performance. Accordingly, it gives implication in decreasing employee performance which has been moderated by high organizational commitment. (7) Accountability gives positive and significant impact in improving employee performance which is moderated by organaizational commitment. It means that the improvement of accountability affects the improvement of employee performance after it is moderated by high organizational commitment. (8) Fairnessgives positive and significant impact in improving employee performance which is moderated by organizational commitment. It means that high fairness affects in improving employee performance and it is strengthened by high organizational commitment.Key words: Good Corporate Governance, employee performance, and organizationalcommitment.